Gaya Bahasa dalam Cerpen Pilihan Kompas 2018 “Doa Yang Terapung” dan Pemanfataannya dalam Pembelajaran Prosa Fiksi di Sekolah Menengah Atas - Nur Rohmah, Sari; Rakhmawati, Ani; Wardani, Nugraheni Eko (GERAM: Gerakan Aktif Menulis, 2022)
This study aims to describe and explain the use of language style in two short stories "Aroma Doa Bilal Jawad" and "Kapotjes and Batu Terapung" in Kompas Choice Short Story 2018 "Floating Prayer". The results of language style analysis in both short stories are also intended to find out its relevance as a teaching material of fictional prose for high school students. This research uses a descriptive qualitative approach. Taking research subjects using purposive sampling technique. The data validity test used source triangulation and theory triangulation. This study uses flow data analysis techniques (flow model of analysis). The results showed that there were 12 types of language style with the frequency of data use in the two short stories as many as 54 data. Mesodiplosys and anaphora were the most dominant styles used, with percentages of 22.2% and 20.37%. Anadiplosys style, metonimies style, and hyperbolic language style are the least used language styles, with a percentage of 1%. The results of the analysis concluded that the Kompas 2018 Choice of Short Story Collection (Floating Prayer), especially in the short story titled "Aroma Doa Bilal Jawad", and "Kapotjes and Batu Yang Terapung" are said to be relevant and can be used as literary learning materials in grade XI high school students